KAJIAN PUSTAKA: TANTANGAN DAN PELUANG PENERAPAN SAK EMKM DI WILAYAH KEPULAUAN DAN PERBATASAN - Litualy, Janet Wilsye (Jurnal Akuntansi Kompetif, 2025)
This study examines the challenges and opportunities in implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in island and border regions, focusing on Maluku Barat Daya District. Based on a literature review of journals, research reports, and policy documents, three major barriers are identified: technical (limited accounting knowledge), structural (restricted access to technology and infrastructure), and cultural (low awareness of formal bookkeeping). Nevertheless, strategic opportunities exist through local adaptation of SAK EMKM, community-based training, and collaboration with universities via MBKM and thematic community service programs. The findings emphasize the need for a contextual accounting model aligned with the socio-cultural realities of island communities. Keywords: SAK EMKM, island regions, MSMEs, simple accounting, financial literacy